Endoscopic and Microsurgical Anatomy of the Cranial Base - Seeger, Wolfgang; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
This atlas illustrates the anatomical structures of the internal and external cranial base and their topography essential to transnasal endoscopic surgical approaches. Currently, the majority of transnasal microsurgical interventions are largely restricted to hypophyseal interventions. The petrous part of the temporal bone and the retrosellar median area have only been cautiously approached using microsurgical endoscopy due to a current lack of technical experience and topographical knowledge. These approaches are common in the US, though, where they are already successfully conducted which calls for a profound anatomical knowledge. Thus the author focuses on the cranial base and the different approaches in order to prepare surgeons for these interventions. Several anatomical variants and special surgical aspects are presented. The excellent drawings base upon anatomical preparations, cadaver dissections and intra-OP demonstrations collected in the course of the author's decades of neurosurgical experience.
Survey -- Cavum Nasi and Fossa Pterygopalatina -- Sinus Sphenoidalis and Fossa Pterygopalatina -- Tuba Auditiva (Eustachii) -- Pyramis (Petrous Bone, Pars Petrosa Plus Pars Tympanica) -- Clivus Area and Pars Condylaris -- Special Surgical Aspects Examples.
Keywords: Medicine; Human anatomy; Neurosurgery; Medicine & Public Health; Neurosurgery; Anatomy